Smoking and Tobacco-Free Policies in Women’s Residential Substance Use Disorder Treatment Facilities: A Community-Engaged Approach - Fallin-Bennett, Amanda (Nicotine Tob Res, 2018)
INTRODUCTION: The purpose of this study was to (1) describe the role of smoking in the lives of women in residential substance use disorder (SUD) treatment and (2) explore perceptions of the facilitators and barriers to tobacco-free policy among women in residential SUD treatment. METHODS: This was a community-engaged study using qualitative descriptive methods. We first recruited women in a residential SUD treatment facility to participate on a community research team. Interviews with staff (N = 10) and focus groups with clients (N = 42) were conducted using guides informed by the community research team. Interviews and focus groups were analyzed using content analysis. RESULTS: There were two themes related to the role of smoking in the women’s lives: (1) smoking facilitates socialization and (2) smoking as a coping mechanism. There were three themes related to the benefits of tobacco-free policy: (1) improved health, (2) support for continued abstinence from a previous tobacco-free placement (eg, prison), and (3) less grounds up-keep. Barriers to tobacco-free policy included (1) lack of an alternative coping mechanism to smoking, (2) fear that a tobacco-free policy would drive clients away, and (3) anticipation of implementation challenges. CONCLUSIONS: Many women in residential SUD treatment smoke, which they attribute to the fact that smoking is used to facilitate socialization and cope with stress. Future research is needed to develop and test messages to counter the misperception that smoking is an effective method to cope with stress. Ultimately, evidence-based tobacco-free policies are needed to reduce tobacco-related disease among women with SUDs. IMPLICATIONS: To promote smoking cessation among women with substance use disorders through evidence-based tobacco policy, it is necessary to first understand the role of smoking in their lives as well as facilitators and barriers to tobacco-free policy in residential treatment facilities. Participants reported that smoking facilitated socialization and served as a coping mechanism. Tobacco-free policies have many benefits, including improved health, support for continued abstinence from a previous tobacco-free placement (eg, prison), and less grounds up-keep. Barriers include the lack of an alternative coping mechanism, fear that a tobacco-free policy would drive away clients and anticipation of implementation challenges. To reduce the burden of tobacco-related morbidity and mortality among women and their children, it is necessary to catalyze a culture change in behavioral health settings to prioritize the treatment of tobacco alongside treatment of other addictions.